1999
DOI: 10.1136/jcp.52.8.574
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumour associated antigen immunoreactivity and apoptosis in cerebral glioblastomas: an analysis of 168 cases.

Abstract: Aims-To evaluate a possible association between clinical outcome in patients with glioblastoma and expression of some immunohistochemical variables and apoptosis. Methods-168 selected patients with cerebral glioblastomas were studied retrospectively. Tumour specimens were examined immunohistochemically with antibodies to proliferating cell nuclear antigen (PCNA), p53, bcl-2, and epidermal growth factor receptor (EGFR) to detect the intracellular receptor domain. Apoptosis was detected by in situ end labelling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 42 publications
3
36
1
Order By: Relevance
“…Two recent papers have found a positive association between apoptotic index and survival Nakamizo et al, 2002). Earlier studies also showed an improved survival with increased apoptosis (Korshunov et al, 1999 andRhodes, 1998) although others have not found such a relationship (Heesters et al, 1999 andNakamura et al, 1997). This inconsistency of results may be related to the variable identity of apoptotic cells, which has not been widely recognized.…”
Section: Discussionmentioning
confidence: 91%
“…Two recent papers have found a positive association between apoptotic index and survival Nakamizo et al, 2002). Earlier studies also showed an improved survival with increased apoptosis (Korshunov et al, 1999 andRhodes, 1998) although others have not found such a relationship (Heesters et al, 1999 andNakamura et al, 1997). This inconsistency of results may be related to the variable identity of apoptotic cells, which has not been widely recognized.…”
Section: Discussionmentioning
confidence: 91%
“…31,32 Several molecular markers have been proposed, including LOH of chromosome 10 and the overexpression of EGFR--both of which are correlated with a poor prognosis. [33][34][35] To learn more about the roles of SOX5 antibody responses in GBM patients, we compared the survival of antibody-positive patients with that of antibody-negative patients. Kaplan-Meier plotting showed that the survival of GBM patients with SOX5 IgG was significantly prolonged, compared to that of SOX5 IgG-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because patient age is a continuous variable, the cut-off age that subdivided patients best into distinct survival groups was determined according to Korshunov et al 21 Consequently, it was determined that the cut-off age of 40 years was the strongest predictor of outcome (5-year survival rate, 34% for younger patients compared with 6% for older patients; log-rank test; P ϭ 0.0002). We were unable to draw any significant association between the overall survival and other clinical variables, including tumor location (frontal vs. nonfrontal), volume of resection (total/ subtotal vs. partial), and various regimens of chemotherapy.…”
Section: Clinical Variables and Follow-up Datamentioning
confidence: 99%